A Lesson in Trust Yields Big Rewards in Panama Procurement : $20 Million Saved in One Contract in 2009 Alone - World Bank (Washington, DC, 2012)
This brief includes the following heading: introduction; a bottom-up success; fuel for the future; procurement: where the rubber hits the road; and miles to go.